Characterization of antinutrients in four silages of taro (Colocasia esculenta (L.) Schott) for pigs. Technical note - Caicedo, W.; Rodríguez, R.; Lezcano, P.; Ly, J.; Vargas, J. C.; Uvidia, H.; Valle, S.; Flores, L. (Cuban Journal of Agricultural Science, 2017)
A total of 48 micro-silos of 2 kg capacity of taro tubers were used, distributed in four treatments (natural yogurt, whey, 5% sugarcane molasses B and 10% sugarcane molasses B), according to a completely randomized design, with the objective of characterizing the main antinutrients for pig feeding. In all silos, during the six days of research (0, 1, 2, 3, 4 and 5 d), the results showed that there were no significant differences (P > 0.05) for the calcium oxalate content. The alkaloids had a moderate (++) condition at day zero, and from the first to the fifth day they were present (+), there were absence (-) of flavonoids, tannins and saponins. According to the results, it is considered that the four silages of taro tubers have adequate antinutrient characteristics for their use in alternative pigs feeding. Key words: food for pigs, fermentation , molasses B, calcium oxalate, natural yogurt.